2020
DOI: 10.3390/ijerph17196962
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Driving Intention Transitions Caused by Driver’s Emotion Evolutions

Abstract: Joining worldwide efforts to understand the relationship between driving emotion and behavior, the current study aimed at examining the influence of emotions on driving intention transition. In Study 1, taking a car-following scene as an example, we designed the driving experiments to obtain the driving data in drivers’ natural states, and a driving intention prediction model was constructed based on the HMM. Then, we analyzed the probability distribution and transition probability of driving intentions. In St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 72 publications
(75 reference statements)
0
9
0
Order By: Relevance
“… 40 For the eight typical driving emotions mentioned above, we proposed an experimental framework for driving emotion induction in our previous researches. 36 , 37 The emotion inductions in this experimental framework contained preliminary induction, in-depth induction, driving context assumption and emotional experience reminder. The induction methods used in the preliminary induction included emotional pictures induction (for anger, surprise, fear and anxiety), personalized recall (for helplessness, contempt and relief) and prizes induction (for pleasure).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 40 For the eight typical driving emotions mentioned above, we proposed an experimental framework for driving emotion induction in our previous researches. 36 , 37 The emotion inductions in this experimental framework contained preliminary induction, in-depth induction, driving context assumption and emotional experience reminder. The induction methods used in the preliminary induction included emotional pictures induction (for anger, surprise, fear and anxiety), personalized recall (for helplessness, contempt and relief) and prizes induction (for pleasure).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, 36 , 37 we have determined the eight most common emotions in driving activities, ie, anger, surprise, fear, anxiety, helplessness, contempt, relief and pleasure. In this study, we mainly studied the effects of these eight emotions and self-reported individual traits on the actual risky driving behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [10] evaluate the effects of TOR phases by analyzing the driver's gaze, Heart Rate (HR), Galvanic Skin Response (GSR), and facial expression. In [11], a Hidden Markov Model (HMM), which uses speed and distance between vehicles, is employed to estimate a driver's behavior with specific induced emotions. A study that compares the car driver's stress in a simulated autonomous and manual driving scenario, using an SVM algorithm, was introduced in [12].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the vehicle is subject to many constraints, such as road conditions and surrounding moving targets. On the other hand, affected by the driver's driving intention and style [1], the trajectory tends to be highly nonlinear over time. These challenges have caused the degradation of both traditional dynamic models and machine learning models Therefore, trajectory prediction methods based on deep learning have become a current research hotspot.…”
Section: Introductionmentioning
confidence: 99%